2020
DOI: 10.1177/2280800020966936
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nano-filler based experimental dentine adhesive. A SEM / EDX, Micro-Raman and microtensile bond strength analysis

Abstract: Aim: The study aimed to assess graphene oxide (GO) adhesive and its dentin interaction using scanning electron microscopy (SEM), MicroRaman spectroscopy and Microtensile bond strength (μTBS). Materials and Methods: Experimental GOA and control adhesives (CA) were fabricated. Presence of GO within the experimental adhesive resin was assessed using SEM and Micro-Raman spectroscopy. Ninety specimens were prepared, sixty teeth were utilized for μTBS, twenty for SEM analysis of interface for CA and GOA and ten were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Another important issue is the loss of minerals from the resin‐dentin interface that leads to the biodegradation of the bond, ultimately leading to restorative failure (Wang, Spencer, & Yao, 2006). To improve the performance of adhesives, the addition of inorganic fillers inside adhesive's composition has been encouraged (Belli et al, 2014) as these fillers can decrease solubility of the adhesive (Itoh et al, 2010) and can also augment mechanical properties of the adhesive (Alshahrani et al, 2020). Furthermore, the addition of biomaterial‐based inorganic fillers can remineralize resin‐dentin bond, increasing longevity of the material (Niu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue is the loss of minerals from the resin‐dentin interface that leads to the biodegradation of the bond, ultimately leading to restorative failure (Wang, Spencer, & Yao, 2006). To improve the performance of adhesives, the addition of inorganic fillers inside adhesive's composition has been encouraged (Belli et al, 2014) as these fillers can decrease solubility of the adhesive (Itoh et al, 2010) and can also augment mechanical properties of the adhesive (Alshahrani et al, 2020). Furthermore, the addition of biomaterial‐based inorganic fillers can remineralize resin‐dentin bond, increasing longevity of the material (Niu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 One of the approaches is to incorporate bioactive inorganic fillers in the adhesive. 4 The literature shows evidence of successfully incorporating these fillers in the adhesive with desired outcomes. 5 Previously, hydroxyapatite (HA), 6 silica, 7 and graphene oxide (GO) 8 fillers have been shown to reinforce the mechanical properties of dentin adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome failure of adhesion over time, addition of inorganic fillers in adhesives is promoted to improve dentin interaction of adhesive resins and possibly minimize dentin-adhesive degradation [ 7 ]. Previous studies have shown that addition of fillers in adhesives can reduce water sorption and solubility [ 8 ], in addition to enhancing its mechanical properties [ 9 ]. Therefore, addition of inorganic nano-materials as fillers to develop the physical and mechanical properties of dentin adhesive’s is highly desirable.…”
Section: Introductionmentioning
confidence: 99%